Cultivating livability: Food, class, and the urban future in Bengaluru - Frazier, Camille (London University of Minnesota press, 2024)
What makes for a livable life, and for whom? Taking Bengaluru, India, as a case study, Camille Frazier probes the meaning of "livability" by exploring the food networks connecting peri-urban farmers and the middle-class public. Examining the varying efforts to reconfigure processes of food production, distribution, retail, and consumption, she demonstrates how these intersections are often rooted in and exacerbate ongoing forms of disenfranchisement that privilege some lives at the expense of others
Keywords: Food security India Bangalore; Urbanization India